2013
DOI: 10.1093/mnras/stt137
|View full text |Cite
|
Sign up to set email alerts
|

Multiplanet destabilization and escape in post-main-sequence systems

Abstract: Discoveries of exoplanets orbiting evolved stars motivate critical examinations of the dynamics of N -body systems with mass loss. Multi-planet evolved systems are particularly complex because of the mutual interactions between the planets. Here, we study the underlying dynamical mechanisms which can incite planetary escape in two-planet post-main sequence systems. Stellar mass loss alone is unlikely to be rapid and high enough to eject planets at typically-observed separations. However, the combination of mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 68 publications
2
76
0
Order By: Relevance
“…We consider the possible implications of the stellar mass loss for planetary dynamics and show that, for small values, the stability of the planetary motion is not affected. This result is in agreement with the results obtained by Voyatzis et al (2013), which showed that the planetary motion is destabilized when the loss of the stellar mass reaches 10%.…”
Section: Introductionsupporting
confidence: 93%
“…We consider the possible implications of the stellar mass loss for planetary dynamics and show that, for small values, the stability of the planetary motion is not affected. This result is in agreement with the results obtained by Voyatzis et al (2013), which showed that the planetary motion is destabilized when the loss of the stellar mass reaches 10%.…”
Section: Introductionsupporting
confidence: 93%
“…For instance, gravitational interactions between the planets can play an important role during the subgiant phase, although they tend to destabilize the system (Voyatzis et al 2013;Veras et al 2013;Mustill et al 2014). However, mean motion resonances (MMR) can help the inner orbit to migrate outward and thus escape being engulfed by the star, as in the formation of the solar system (e.g., Levison & Morbidelli 2003;D'Angelo & Marzari 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Initially focusing on the future of the solar system (Sackmann et al 1993;Duncan & Lissauer 1998), a number of theoretical studies have shown that a fraction of planets can survive the red-giant stage Table 1 is available in electronic form at http://www.aanda.org of their host stars (Villaver & Livio 2007, 2009Nordhaus et al 2010;Mustill & Villaver 2012). The ensuing long-term orbital evolution is complex and may lead to planet ejections or collisions (Debes & Sigurdsson 2002;Veras et al 2011;Voyatzis et al 2013). Smaller bodies are likely to be scattered, from locations comparable to the solar system's main asteroid belt or Kuiper belt Debes et al 2012), which will lead to their tidal disruption if their trajectory takes them within the Roche radius of the white dwarf, ≈1 R , (Davidsson 1999).…”
Section: Introductionmentioning
confidence: 99%